Influence of negative stereotype on physical activity level among older adults during a training session - Deshayes, Maxime; Palermo, Angèle; Korchi, Karim; Philippe, Antony G. (Frontiers in Sports and Active Living, 2022)
The present research examined the effect of a negative stereotype induction on older adults’ physical activity level, measured objectively and subjectively. Twenty older adults (18 women and 2 men; Mage = 67.4, SDage = 4.4) were assigned to a control condition, a neutral condition and a negative stereotype condition during three separate visits (i.e., within-subject design). In each physical activity session, participants performed the same training. Objective physical activity level was the time spent at moderate to vigorous intensity measured by accelerometry and subjective physical activity level was measured with the RPE-session method. Inactivity time was also objectively assessed. Results revealed no effect of the different conditions on objective physical activity level, but subjective physical activity level and inactivity time were lower in the neutral condition and in the negative stereotype condition compared to the control condition. It was suggested that when a negative stereotype is induced, participants perceived the task as less intense compared to the control condition, which result in less inactivity time, suggesting that the negative stereotype had a positive influence on physical activity. Another interesting result was that effects were similar in the negative stereotype condition and in the neutral condition, revealing that the neutral condition might not be a control condition. While these results are not in line with the stereotype threat literature, they echo previous recent studies also showing a positive effect of a negative stereotype induction, calling into question the stereotype threat theory.